Global Financial Crises and its Impact on Banking Sector in Pakistan - Phulpoto, Lutuf Ali; Shah, Aisha Bashir; Shaikh, Faiz Muhammad (Journal of Asian Business Strategy, 2012)
The research investigates the performance of Islamic banking in Global economic recession period in Compare with Conventional Banking from the period of September 2008b to December 2009 in Pakistan. Data were collected from four leading Islamic banks and Four Conventional banks from the period of Sept.2008 to December 2009 operated in Pakistan. It was revealed that Islamic banking has more growth in the recession period in Pakistan. The main reason of slow growth of Islamic banking is due to unawareness among the customers and the conventional banks in Pakistan has longer history and experience in doing the banking business and holding dominant position in the financial sector in Pakistan. The financial ratios such as return on Assets (ROA), return on Equity (ROE), Loan to Deposit ratio (LDR) Loan to Asset Ratio(LAR) Debt to equity Ratio(DER), Assets Utilization(AU), and Income to Expense ratio(IER) are used to assess banking performance. T test and F-test were used in determining the significance of results. It was revealed that Islamic banking is less profitable, less risky and less efficient compare with the conventional banking in Pakistan during the study period 2007- to marchKey implication of current study to analyze the impact of Global Economic Recession wave affected the Banking sector in Pakistan in general and Islamic banking particular. This research also provides the guide line for the investors to invest in Islamic banking.This study contributes and explores the opportunities for the customers and investors to invest in the Islamic banking because that is less risky compare with the Conventional banking in Pakistan.